2017
DOI: 10.21873/invivo.11103
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1 and MicroRNA-21 Individually Regulate Cellular Growth of Non-malignant and Malignant Renal Cells

Abstract: Abstract. Background/Aim: Due to its poor prognosis, it is increasingly necessary to understand the biology of renal cell cancer (RCC). Therefore, we investigated the role of microRNAs miR-1 and miR-21 in the growth of RCC cells compared to that of non-malignant renal cells. Materials and Methods: Four malignant cell lines RCC4, A498) Tumorigenesis gives cells an advantage in survival by an increase of proliferation, angiogenesis, immunomodulation and immortality (1-4). Due to its delayed diagnosis until ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…All three cell lines showed slightly different effects after treatment with Triton X-100 in the FDA-uptake assay as well as the FDA-release assay. As already determined in other studies (15,16), the membrane-permeabilizing effect of Triton X-100 was not different between malignant and non-malignant renal cells. It can therefore be assumed that both the FDA-uptake test and the FDA-release test can be performed with cancer cells as well as with normal cells.…”
Section: Discussionsupporting
confidence: 81%
“…All three cell lines showed slightly different effects after treatment with Triton X-100 in the FDA-uptake assay as well as the FDA-release assay. As already determined in other studies (15,16), the membrane-permeabilizing effect of Triton X-100 was not different between malignant and non-malignant renal cells. It can therefore be assumed that both the FDA-uptake test and the FDA-release test can be performed with cancer cells as well as with normal cells.…”
Section: Discussionsupporting
confidence: 81%
“…microRNA-1-3p (miR-1-3p) was found as a novel marker and plays as a tumor growth and migration suppressor in urinary system tumors such as bladder cancer14 and prostate cancer 15. Previous preliminary reports showed that miR-1, a homologous analog of mir-1-3p, may reflect RCC heterogeneity 16. Kawakami et al,17 speculated through preliminary in vitro experiments that mirR-1 might be related to apoptosis and cycle arrest of RCC.…”
Section: Introductionmentioning
confidence: 99%
“…The implication of miR-21 in the progression of renal cell cancer (RCC) was also established [118]. Regarding nasopharyngeal carcinoma, miR-21 expression proved to be up-regulated in advanced stages and was also correlated with the presence of metastatic adenopathy.…”
Section: Mir-21mentioning
confidence: 99%